Fuel efficiency‐oriented platooning control of connected nonlinear vehicles: A distributed economic MPC approach. Issue 4 (18th February 2019) - He, Defeng; Qiu, Tianxiang; Luo, Renshi
Abstract: This paper considers the fuel efficiency‐oriented platooning control problem of connected vehicles. We present a novel distributed economic model predictive control (EMPC) approach to solve the problem of the vehicle platoon subject to nonlinear dynamics and safety constraints. In order to improve fuel economy of the whole vehicle platoon, the fuel consumption criterion is used to design the distributed EMPC strategy for the platoon. Meanwhile, the car‐tracking performance is exploited to guarantee stability and string stability of the platoon. Then the fuel efficiency control problem of the platoon is formulated as a distributed dual‐layer economic optimal control problem, which is solved in a fashion of receding horizon. It is proved that the proposed strategy guarantees asymptotic stability and predecessor‐follower string stability as well as fuel economy of the whole platoon by minimizing the fuel consumption cost. Finally, the effectiveness of the proposed strategy is highlighted by comparing its performance with that of the traditional distributed MPC strategy in numerical simulations.